Visual Function for Driving in Diabetic Macular Edema and Retinal Vein Occlusion Post-Stabilization with Anti-Vascular Endothelial Growth Factor - Nixon DR (Dove Medical Press, 2021)
Donald R Nixon,1– 4 Nicholas Flinn1 1Trimed Eye Centre, Barrie, Ontario, L4M 4S5, Canada; 2Department of Surgery, Royal Victoria Regional Health Centre, Barrie, Ontario, Canada; 3Department of Surgery, Soldiers Memorial Hospital, Orillia, Ontario, Canada; 4Department of Surgery, Northern Ontario School of Medicine NOSM, Sudbury, Ontario, CanadaCorrespondence: Donald R NixonTrimed Eye Centre Barrie Ontario, 190 Cundles Road East Suite 100c, Barrie, Ontario, L4M 4S5, CanadaTel +1 705 737 3737Email Trimedeyedoc@gmail.comPurpose: What is the level of visual function in patients with diabetic macular edema (DME) and retinal vein occlusion (RVO) post-stabilization with anti-vascular endothelial growth factor?Patients and Methods: This observational non-controlled single center study evaluated visual function in two patient populations with macular edema 25 with diabetic macular edema and 25 with retinal vein occlusion treated following standard protocol of anti-VEGF therapy post- stabilization.Results: A total of 68 eyes from 50 patients were analyzed including 18 bilateral and 7 unilateral diabetic macular edema, 14 patients with central and 11 with branch retinal vein occlusion. The mean age was 69± 11 years and 64% were male. In the RVO group: LogMAR BCVA was 0.12± 0.13 compared to the unaffected eye 0.04± 0.05 (P=< 0.01), contrast sensitivity in the treated eye was 1.69± 0.21 log units compared to 1.84± 0.15 log units in the unaffected eye (p=< 0.01), the ganglion cell volume was 0.88± 0.15 mm3 in the treated eye compared to 1.04± 0.1 mm3 in the unaffected eye (P=< 0.01). In the diabetic macular edema group: LogMAR BCVA was 0.17± 0.13, contrast sensitivity in the treated eye was 1.16± 0.21 log units compared to the normal population 1.92± 0.8 log units (p=< 0.01), the ganglion cell volume was 0.94± 0.14 mm3 in the treated eye compared to 1.03± 0.12 mm3 in the normal population (P=< 0.001). In both groups a majority of treated eyes retained visual acuity ≥+0.4 LogMAR (diabetic macular edema 95%, RVO 96%) however contrast sensitivity was more than two standard deviations below the normal population mean in a majority of treated eyes in both groups (diabetic macular edema 88% RVO 64%).Conclusion: Impairment in contrast sensitivity in both groups could impact activities of daily living including driving and should prompt questions about how we advise patients regarding their level of function and the potential limitations/restrictions that should be placed on such activities.Keywords: contrast sensitivity, residual deficit, functional impairment